Impact of replacing the old chicken and add soy protein in Alvezaawih qualities Barker beef (Baghdad Science Journal, 2006)
The purpose of this study was to determine the impact of added soy protein humidifier concentration of different ratios of bovine Alberkr mix that was to bring the old chicken shop pure beef in five ratios